The Bible and African culture : mapping transactional inroads - Waweru, Humphrey (Eldoret, Kenya : Zapf Chancery, 2011)
How can African theology survive the self-repetition of mere cultural apologia or contextualization-stereotypes, and mature into a critical theoretical discipline responding to the challenges of the postmodern world-order? Dr. Humphrey M. Wawe contributes here a sound theological reflection using the hitherto unused methodological paradigm of mapping the inroads in the "transaction" between the Bible and African culture.
Preface -- Introduction -- Chapter One: African culture and the Bible -- Chapter Two: Kikuyu people -- Chapter Three: Mapping the transaction between African culture and the Bible -- Chapter Four: Methodologies for transaction between African culture and the Bible -- Chapter Five: Inter-religious transaction between African culture and the Bible -- Chapter Six: African culture and the Bible transact in worship and mission -- Chapter Seven: The place of women in this transaction with reference to John's Gospel -- Chapter Eight: Dowry: African or Christian? Another inter-religious transaction -- Chapter Nine: Revelation.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Christianity and culture -- Africa; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Christianity and culture; Africa; RELIGION / Christian Theology / General; Electronic books